Support for biodiversity former military site [Tender documents : T24695392] (MENA Report, 2014)
The subject of the public contract is to undertake actions that lead to the promotion of biodiversity botanical and zoological valuable territory and to stop the degradation of valuable communities and protected species due to spontaneous succession and spread of invasive and expansive plant species. In the area of ??interest will be established pastoral areas, since for a given area seems like the perfect year-round breeding free when it is not needed winter stabling.